Integrated Strategy of the Output Planning and Economic Operation of the Combined System of Wind Turbines-Pumped-Storage-Thermal Power Units - Liye Ma; Zhiqiang Wang; Zhigang Lu; Xiaoyu Lu; Furui Wan (IEEE Access, 2019)
Aiming at the problem that the large-scale renewable energy is integrated into the grid, which causes the instability of the system output power, the optimal scheduling of the power system during operation, system stability, and power quality. Based on the construction of wind power-pumped storage combined generator set by using water resources, combined with the power generation of a thermal power unit, a scheduling strategy based on the dynamic Kriging model for the integrated strategy of output planning and the economic operation of a wind power-pumped storage-thermal power combined system is proposed. The strategy uses the hypercube sampling method and the particle swarm optimization algorithm after improving the inertia weight to solve the model. The simulation results verify the correctness and effectiveness of the proposed strategy. Through the strategy proposed in this paper, the best output operation scheme of the combined system can be obtained at the same time, which reduces the total investment cost of the system and increases the consumption of renewable energy.